Acardiac-acephalus Twinning- A Very Rare Case Report (Medicine Today, 2020)
Introduction:This study highlights a very rare case which was related to abnormal monochorionic twinning status.Case Report: This case (a 28 year old pregnant woman) came at this institute for ultrasonographic evaluation of herpregnancy status. Her ultrasonographic results were consistent with acardiac-acephalus twinning condition (which isalso known as, twin reversed arterial perfusion or TRAP sequence).Discussion: This monochorionic twin pregnancy isa severe form of twin-to-twin transfusion syndrome (TTTS) and severe TTTS has mortality rate of about 60–100%.Conclusion: This case is very rare showing prevalence of about 1/35,000 overall pregnancies and accounting 1.0% ofthe monochorionic twin pregnancies.Medicine Today 2020 Vol.32(2): 143-144